Perbedaan Angka Kebersihan Gigi dan Mulut (HI) Anak Umur 12 Tahun yang Menyikat Gigi dengan Teknik Kombinasi Fone’s Horizontal dan Roll Horizontal di SDN 06 dan 21 Taluak IV Suku - Nova Herawati; Rahma Setyani; Aflinda Yenti; Aljufri Aljufri; Ika Ifitri; Syukra Alhamda (Poltekkes Kemenkes Padang, 2024)
Dental caries is the most common oral health problem experienced by the public, with plaque being the main cause. Brushing teeth is an effective method for removing plaque, where the brushing technique plays a crucial role in oral hygiene. Elementary Schools (SDN) 06 and 21 Taluak IV Suku regularly receive visits from the local health center every six months for dental check-ups. SDN 06 has never conducted a mass tooth brushing activity, while SDN 21 does it routinely every Wednesday, guided by trained student health officers. Preliminary studies showed that 60% of the children from both schools brush their teeth once a day using a horizontal technique. This study aims to compare the oral hygiene of 12-year-old children who use the combination of Fone’s-horizontal technique and the combination of roll-horizontal technique. The research design is a quasi-experimental study with pretest and posttest. The population consisted of 50 children, with 48 samples taken using the saturated sampling technique. Dental hygiene was measured using the Hygiene Index, and data were analyzed using the independent t-test (α < 0.05). The results showed an average improvement of 16% for the Fone’s-horizontal technique and 36% for the roll-horizontal technique, with a p-value of 0.000 (< 0.05). In conclusion, the roll-horizontal combination technique is more effective, and children are advised to brush their teeth using this technique twice a day to prevent dental and oral diseases.